Influence of pretreatment solution on the drying of sour cherry - Doymaz, Ibrahim (ELSEVIER SCI LTD, 2007)
The effect of alkali ethyl oleate solution (AEEO) on drying time of sour cherry was studied experimentally. The thin-layer drying of sour cherries was carried out under two air temperatures of 55 and 65 degrees C at a constant airflow velocity of 1 m/s. Drying time of pre-treated samples was about 26-30% shorter than that of untreated samples. The experimental moisture loss data were fitted to select semi-theoretical and empirical thin-layer drying models, namely, Lewis, Henderson and Pabis, Page, Logarithmic, Two-term, Two-term exponential, Wang and Singh, and Midilli et al. models. Three statistical tools were used to quantify the goodness of fitting: the coefficient of determination (R-2), reduced chi-square (chi(2)) and root means square error (RMSE). R-2, chi(2) and RMSE values of all models were compared, it was concluded that the Midilli et al. and Logarithmic models were found to be most suitable in describing the drying characteristics of sour cherry. Effective moisture diffusivity of sour cherries based on analytical solution of Fick's second law ranged from 4.75 x 10-(10) to 1.03 x 10(-9) m/s. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: drying; alkali ethyl oleate solution; sour cherry; thin-layer drying models; ETHYL OLEATE; LAYER; MODEL; PARAMETERS; KINETICS; Engineering; Food Science & Technology